Conceptual analysis and normative inquiry in sport : a cautionary note - Morgan, William John (Array, 2020)
Bernard Suits’s classic definitions of games and sport have been widely credited as important philosophical achievements. I share that laudable view of his definitional work. But in this essay I warn against a growing tendency in the philosophy of sport literature to gloss Suits’s definition of these key concepts as metaphysical achievements as well, as discoveries of the true essences of games and sport. I focus my critical attention on the most recent example of such metaphysical overreach, Colin McGinn’s account of games featured in his recent book, Truth by Analysis: Games, Names, and Philosophy. I argue that McGinn’s metaphysical interpretation of Suits’s conceptual analysis of games and sport is ill conceived and examine the normative fallout of interpreting Suits in this way.